KEHIDUPAN SOSIAL EKONOMI MASYARAKAT NELAYAN DI KELURAHAN KARAN AUR KECAMATAN PARIAMAN TENGAH KOTA PERIAMAN (2000-2010) - Ayu, Intan Chindri; Nurhuda, Ahmad; Yulia, Refni (Pendidikan Sejarah, 2013)
ABSTRACTÂ The background of this research is to see the fishermen Karan Aur doing business in meeting the needs of family and economic life Economic life is limited so that the needs of fishing communities less accomplished family. The lives of the fishermen who are always categorized as poor. Based on this, the focus of the research problem posed was